Between Phasmas and Fales: description, figurability and editing in Georges Didi-Huberman’s essays - de Oliveira, Eduardo Jorge (Escritura e Imagen, 2025)
Beyond their entomological origin, phasmids and moths are figures of instability that bring writing into dialogue with images. Between description, figurability, and montage, this essay proposes a reading of two works by Georges Didi-Huberman: Phasmes (1998) and Phalènes (2013). The texts in these two books deal with apparitions, with a kind of writing that, without necessarily describing, carries a vivarium of images.
Keywords: description; figurability; montage; images; detail